Ососбливості трактування постаті Єремії Вишневецького в художній літературі (на матеріалі романів І. Нечуя-Левицького „Князь Єремія Вишневецький” та Г. Сенкевича „Вогнем і мечем”) - Герман, Наталія; Herman, Nataliia (Волинський національний університет імені Лесі Українки, 2008)
У статті досліджуються особливості трактування історичної постаті Єремії Вишневецького в художній літературі України та Польщі. Об’єктом дослідження є князь Вишневецький в історичних романах Г. Сенкевича “Вогнем і мечем” та І. Нечуя-Левицького “Князь Єремія Вишневецький”. The article deals with features of treatment of historical person Jeremi Wiśniowecki in the Ukrainian and Polish literature. The object of research is a person of earl Wiśniowecki in the historical novels by H. Sienkiewicz „With Fire and Sword”and I. Nechuj-Levickij „The Earl Jeremi Wiśniowecki”
The Features of Treatment of Historical Person Jeremi Wiśniowecki in the Literature (on the Material of Novels by I. Nechuj-Levickij „The Earl Jeremi Wiśniowecki” and H. Sienkiewicz „With Fire and Sword”).
Keywords: історичний роман; historical novel; образ; feature figure; портрет; portrait; трактуваня; treatment; модель; model